Postpartum Macrophage Activation Syndrome with Temporal Dissociation of Cytopenias in a Patient with Kikuchi-Fujimoto Disease and UCTD: A Case Report - Zhou, Xiying; Li, Jing; Ma, Yanhua; Liang, Xuxia (AME Case Reports, 2026)
Background: Macrophage activation syndrome (MAS) is a life-threatening hyperinflammatory disorder; postpartum MAS is extremely rare and often misdiagnosed due to overlap with sepsis and HELLP syndrome. Kikuchi-Fujimoto disease (KFD) and undifferentiated connective tissue disease (UCTD) may increase susceptibility, but reports are scarce. This case highlights the diagnostic challenges of postpartum MAS in the setting of overlapping inflammatory conditions.Case Description: The patient was a 35-year-old primiparous woman with KFD and UCTD who underwent cesarean section for preeclampsia and cervical insufficiency. She developed septic shock postoperatively. Despite infection control, persistent fever and a distinct temporal dissociation emerged: platelets recovered from 12 to 198×10⁹/L while neutrophils initially remained normal but subsequently declined to 0.04×10⁹/L. Hyperferritinemia (>1500 μg/L), hypertriglyceridemia (3.88 mmol/L), and hypofibrinogenemia (1.78 g/L) developed. The HScore was 176, exceeding the established cutoff of 169 associated with a high probability of reactive hemophagocytic syndrome. Natural killer (NK) cell activity was 2.76% (normal >15%), whereas serum sCD25 was unexpectedly low (